Improving stability in QoS routing for ad-hoc networks - Coelho, Tiago (2014)
Routing in mobile Ad-Hoc networks is normally a difficult task, but even more challenging if the network is expected to provide support for audio and video streaming between human-carried devices. Besides normal movement and signal impairment difficulties, those multimedia applications may impose extra end-to-end requirements. The computation of optimized and/or constrained network paths using one or more metric restrictions is called QoS (Quality-of-Service) routing. This paper presents QMRS, a QoS routing protocol for Ad-Hoc networks which aims to support applications with QoS requirements including requirements for the end-to-end delay. This protocol proposes a on-demand multiple routes discovery mechanism that is able to find up to three node-disjoint paths that meet the QoS requirement. Additionally, and for the purpose of guarantee the stability of the routing process, it uses the signal strength of the links between neighbouring nodes to elect the most stable route. Such route will be used as the primary choice to forward traffic. The other discovered routes will be maintained as backup in order to eventually replace the primary route, in case of disruption or degradation of required QoS. QMRS was implemented in NS-3 and evaluated in comparison with AODV and AMR (an AOMDV-like protocol). Simulation results show significant improvements, with respect to the average end-to-end delay, packet delivery ratio and throughput.